Report on the petroleum field, west Newfoundland [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's, Nfld : [s.n.], 1909)
Report submitted to the Geological Survey Office, St. John's, Nfld. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44